An insight into the effect of Persea Americana as a potassium rich diet on adenine induced renal fibrosis in mice. Issue 1 (1st January 2020) - Shalaby, Mohamed; Abu-Elsaad, Nashwa M; Ibrahim, Tarek M
ABSTRACT: One of the valuable interventions in controlling chronic kidney disease is the dietary management. The study was designed to test effect of Persea Americana on adenine induced kidney injury. Four groups of mice were used: control group; adenine group: received adenine (0.2% w/w) daily with normal chow for 4 weeks; diet I group: received adenine then avocado [50% w/w in food] for 2 weeks; diet II group: received adenine then avocado [100% w/w] for 2 weeks. Serum levels of creatinine and potassium were measured in addition to oxidative stress biomarkers. Renal tissue injury and collagen deposition were scored. Renal expression of TGF-β1, CCL3L1 and IL-2 were assigned. Results showed significant decrease ( p < 0.01) in serum creatinine level in diet I group. Serum potassium was elevated ( p < 0.01) in diet I and II groups. Level of MDA was decreased ( p < 0.01) while reduced glutathione and catalase were elevated ( p < 0.05) by diet I and to a lesser extent by diet II. Both diet I and II markedly reduced fibrosis and tubular injury. Levels of TGF-β1 and CCL3L1 were decreased in both tested groups ( p < 0.001) while IL-2 was increased. Enriching diet with Persea Americana fruit can attenuate renal fibrosis progression through anti-fibrotic, anti-oxidant and anti-inflammatory pathways.